2023
DOI: 10.1002/art.42396
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mechanisms by Which Genetic Susceptibility Loci Influence Systemic Sclerosis Risk Using Functional Genomics in Primary T Cells and Monocytes

Abstract: Objective Systemic sclerosis (SSc) is a complex autoimmune disease with a strong genetic component. However, most of the genes associated with the disease are still unknown because associated variants affect mostly noncoding intergenic elements of the genome. We used functional genomics to translate the genetic findings into a better understanding of the disease. Methods Promoter capture Hi‐C and RNA‐sequencing experiments were performed in CD4+ T cells and CD14+ monocytes from 10 SSc patients and 5 healthy co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Currently, the exact mechanism underlying these dual elements in the same cell type remains unknown. However, there is supporting evidence for a model of enhancer-silencer activity in which the ESpromoter would make direct 3D contact with the promoters of the regulated genes 27 , likely facilitated by TFs and cofactors acting as intermediaries. Cis-regulatory elements are DNA fragments that serve as active hubs to recruit TFs through short DNA motifs to regulate transcription.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Currently, the exact mechanism underlying these dual elements in the same cell type remains unknown. However, there is supporting evidence for a model of enhancer-silencer activity in which the ESpromoter would make direct 3D contact with the promoters of the regulated genes 27 , likely facilitated by TFs and cofactors acting as intermediaries. Cis-regulatory elements are DNA fragments that serve as active hubs to recruit TFs through short DNA motifs to regulate transcription.…”
Section: Discussionmentioning
confidence: 95%
“…Prediction of the interaction between Genehancer regulatory elements and neighboring genes suggested that the ATP2B4 Epromoter may have four target promoters, including ATP2B4 , LAX1 , ZC3H11A, and OPTC (Figure 1A). Promoter capture Hi-C data from CD4+ T cells 27 , revealed a significant T-cell specific interaction between ATP2B4 Epromoter and both LAX1 and ATP2B4 promoters (Figure 1B, Figure S1). However, no significant interaction was detected between the ATP2B4 Epromoter and the ZC3H11A and OPTC genes in CD4+ T cells 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Future genetic studies such as functional genomics studies, which discover new diseaseassociated variants and functionally annotate known genetic risk variants with target genes and regulatory elements, can be incorporated into further iterations of the G-PROB tool, which may further improve its cross-ancestry performance and utility. 38,39 A second limitation relates to power; despite including a sample size nearly four times larger than the original study, 25 we still had relatively low numbers of patients with diagnoses less commonly made in patients with suspected early inflammatory arthritis (including gout) (Figure 1). In the context of NOAR and UK clinical practice, this is likely because patients with gout are diagnosed by clinicians outside of the rheumatology outpatient setting (eg, in primary care or in hospital).…”
Section: Discussionmentioning
confidence: 99%
“…On the same line, promoter capture Hi-C and RNA-sequencing approaches were recently used to link associated variants of systemic sclerosis (a connective tissue immune-mediated disease) with their target genes, especially in CD4+T cells and CD14 + monocytes obtained from 10 patients and five matched healthy controls. The authors identified new potential targets genes and 15 other potential drug targets for repurposing of drugs already in use in other immune-mediated diseases ( Gonzalez-Serna et al, 2022 ).…”
Section: Investigating the 3d Genome In Rheumatic Diseases And Asmentioning
confidence: 99%